Pemanfaatan Energi Terbarukan melalui Instalasi Lampu Jalan Tenaga Surya di Kawasan Pemukiman Pedesaan - Akhyar Muchtar; Dessy Ana Laila Sari; Elfira Makmur; Muh. Iswal Burhan; Wahyudi (Fakultas Teknik, 2026)
This community service program aimed to address the absence of adequate street lighting in rural settlements of Bulukumba Regency, South Sulawesi, which negatively impacts resident safety and comfort during nighttime hours. The Faculty of Electrical Engineering, Universitas Negeri Makassar, implemented solar-powered street lighting (PJUTS) as a renewable, environmentally friendly, and cost-effective infrastructure solution. The methodology comprised four sequential stages: (1) field survey and site selection, (2) equipment procurement and unit assembly, (3) installation on poles at designated locations, and (4) functional testing and evaluation. Three solar street light units were successfully installed, each integrating a monocrystalline photovoltaic panel, LED luminaire, charge controller, and lithium battery. Night-time observation confirmed stable illumination across the targeted road segments. Community members reported improved perceptions of safety and comfort. The program demonstrated that solar street light technology is technically feasible and operationally sustainable for rural infrastructure development, providing a replicable model for similar villages in South Sulawesi.